Coulomb excitation of 66ge - Abrahams, Kenzo (University of Western Cape, 2021)
Philosophiae Doctor - PhD === The Coulomb excitation of 66Ge has been performed for the rst time using \safe" bombarding energies at the HIE-ISOLDE facility at CERN in July 2017. A particle-